2017
DOI: 10.1136/archdischild-2016-311343
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in coeliac disease autoimmunity in childhood: the Generation R Study

Abstract: Ethnic differences in children with CDA are present in childhood. Socioeconomic position, daycare attendance and CMV seropositivity partly explained these differences, which may serve as targets for prevention strategies for CDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…The associations between a priori-or a posteriori-derived early-life dietary pattern adherence scores and celiac disease autoimmunity were analyzed using separate logistic regression models for each of the 5 dietary patterns considered, with the continuous adherence Z score as independent variable and child celiac disease autoimmunity (TG2A negative vs TG2A positive) as dependent variable. The final confounder selection was based on known associations of the covariates with diet and with celiac disease, following principles of causal inference, 2,[30][31][32][33] and also by taking the change in regression coefficient into consideration after including each of the covariates in the regression analysis. On the basis of the latter, 2 regression models were considered for each dietary pattern: a crude model (model 1) and a model adjusted for age at dietary assessment, age of TG2A assessment, sex, and ethnicity (model 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associations between a priori-or a posteriori-derived early-life dietary pattern adherence scores and celiac disease autoimmunity were analyzed using separate logistic regression models for each of the 5 dietary patterns considered, with the continuous adherence Z score as independent variable and child celiac disease autoimmunity (TG2A negative vs TG2A positive) as dependent variable. The final confounder selection was based on known associations of the covariates with diet and with celiac disease, following principles of causal inference, 2,[30][31][32][33] and also by taking the change in regression coefficient into consideration after including each of the covariates in the regression analysis. On the basis of the latter, 2 regression models were considered for each dietary pattern: a crude model (model 1) and a model adjusted for age at dietary assessment, age of TG2A assessment, sex, and ethnicity (model 2).…”
Section: Discussionmentioning
confidence: 99%
“…The ethnicity of the child was determined on the basis of the country of birth of the parents and classified as Western or non-Western, according to the criteria used in a previous study. 30 Maternal age, pre-pregnancy body mass index (BMI), and parity (categorized as nulliparous or multiparous) were assessed at the time of enrollment. TG2A levels of the mother were measured during pregnancy and categorized as TG2A positive or TG2A negative, as described for children.…”
Section: Covariatesmentioning
confidence: 99%
“…Serum antibodies to CMV, EBV were found to be lower in CD patients compared to healthy controls [81]. Jansen et al, found that anti-CMV, EBV, and or HSV-1 IgG levels were inversely correlated with transglutaminase type 2 antibody (TG2A) levels, suggesting a protective impact of these viruses in the pathogenesis of CD [82,83]. The protective role of infections in autoimmunity supports the “hygiene hypothesis”, which proposes that cleaner living environment leads to higher incidence of autoimmune disorders [80].…”
Section: Viral Infections and Induction Of Autoimmunitymentioning
confidence: 99%
“…32 Ethnicity was based on the country where parents were born, according to criteria used in a previous study. 33 Data on maternal income and education level were obtained at enrollment through questionnaires. Classification of income and educational level was based on the classification of Statistics Netherlands.…”
Section: Covariatesmentioning
confidence: 99%